2002
DOI: 10.1097/00024382-200208000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Role of Induced Nitric Oxide in the Initiation of the Inflammatory Response After Postischemic Injury

Abstract: The aim of this study was to investigate the role of inducible nitric oxide (NO) synthase (iNOS) and NO on the modulation of the inflammatory response caused by splanchnic ischemia and reperfusion. A severe model of mesenteric ischemia and reperfusion was produced by subjecting mice to 45 min occlusion followed by reperfusion of the superior mesenteric artery and celiac trunk. In this experimental protocol, wild-type mice treated with GW274150 (5 mg/kg i.p.), a novel, potent, and selective inhibitor of iNOS ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0
10

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 28 publications
4
70
0
10
Order By: Relevance
“…It is noteworthy that one study in which iNOS knockout mice were used and reperfusion was not performed (similar to our protocol) found that injury was severe and angiogenesis in the chronic stage was augmented [45]. This is consistent with our results, and indicates that reperfusion plays a critical role in the outcome [46].…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that one study in which iNOS knockout mice were used and reperfusion was not performed (similar to our protocol) found that injury was severe and angiogenesis in the chronic stage was augmented [45]. This is consistent with our results, and indicates that reperfusion plays a critical role in the outcome [46].…”
Section: Discussionsupporting
confidence: 90%
“…Although NO produced through constitutive NO synthase can be an important protective molecule for the small intestine at the onset of intestinal I/R, 15 over-production of NO through the inducible NO synthase (iNOS), especially under the circumstance of oxidant stress, may prove detrimental. The tight positive correlation between Chiu's score and NO production ( Figure 2D) is consistent with the notion that over-production of NO could be detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that over-production of nitric oxide (NO) in intestinal mucosa tissue following intestinal I/R can aggravate lipid oxidative damage 14,15 and that an increase of endothelin-1 (ET-1) is involved in the pathogenesis of intestinal I/R-induced intestinal mucosal injury. 16,17 Therefore, the current study was undertaken to clarify whether propofol can prevent intestinal mucosa I/R injury, and to investigate its effects on NO, ET-1 release during intestinal I/R, in an in vivo rat model.…”
mentioning
confidence: 99%
“…The continuous actions of these sequential events ultimately lead to necrotic cell death. Reperfusion during ischemia replenishes oxygen supply to the brain tissue, restoring energy and ionic homeostasis to a certain extent but this process actually exacerbates ischemic injury due to elevated production of oxygen-and nitrogen-derived free radicals (9,27). Free radicals confer considerable oxidative stress on the brain during reperfusion due to the high rate of oxidative metabolic activity, high levels of polyunstaturated fatty acids leading to lipid peroxidation and DNA damage (9,10).…”
Section: Inflammation In Strokementioning
confidence: 99%